Budaya Kerentanan dan Kapasitas Masyarakat Kepulauan Mentawai Menghadapi Bencana Gempa Bumi dan Tsunami - Sitorus, Purnama Betty Rosalyna (Jurnal Vokasi Indonesia, 2018)
One of the things that can threaten the national security is the high incidence of disasters. Based on the research, scientists estimate there are still many events including a major earthquake disaster -risk tsunami threat in Indonesia, particularly in the Mentawai Islands which is a 200 year earthquake cycle. One effort to do for disaster risk reduction is by knowing the culture in society, vulnerability, and capacity of communities to cope with disasters. The purpose of this study is to map the culture associated with disasters and analyze the vulnerability and capacity of the social, physical, economic, and environmental. Location of the study was conducted in two villages, the Maileppet Village and Tuapeijat Village. The study used qualitative methods with phenomenological approaches and VCA (Vulnerability and Capacity Analysis) as a tools used to facilitate mapping the vulnerabilities and capacities. The results of this study showed that Uma, the traditional home of Mentawai people are the result of knowledge that can reduce the risk of disaster. Oral storytelling from the ancestors is also known can give knowledge to the villagers how to cope with the disasters. This study also shows that from most aspects of social, economic, physical, and environmental, Tuapeijat villagers and Maileppet villagers are in a vulnerable condition and does not have enough capacity to cope with disasters.